2020
DOI: 10.1002/chem.202000993
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Crystallisation Kinetics of Zr Metal–Organic Frameworks through Turbidity Measurements to Inform Rapid Microwave‐Assisted Synthesis

Abstract: Controlling the crystallisation of metal‐organic frameworks (MOFs), network solids of metal ions or clusters connected by organic ligands, is often hindered by the significant number of synthetic variables inherent to their synthesis. Coordination modulation, the addition of monotopic competing ligands to solvothermal syntheses, can allow tuning of physical properties (particle size, porosity, surface chemistry), enhance crystallinity, and select desired phases, by modifying the kinetics of self‐assembly, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…12 Models based on monomer addition also do not apply to MOFs, as studies suggest MOF formation involves transiently metastable "primary" phases, aggregative growth, and other non-classical events. [13][14][15][16] Although these existing models can be modied to account for non-classical events, nanoMOF research requires a general model based on the acid-base and coordination chemistry of MOFs to reliably predict and control particle sizes.…”
Section: Introductionmentioning
confidence: 99%
“…12 Models based on monomer addition also do not apply to MOFs, as studies suggest MOF formation involves transiently metastable "primary" phases, aggregative growth, and other non-classical events. [13][14][15][16] Although these existing models can be modied to account for non-classical events, nanoMOF research requires a general model based on the acid-base and coordination chemistry of MOFs to reliably predict and control particle sizes.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a complex mixture of mechanisms underpin modulation rather than simple coordinative competition. 42 The importance of water addition in these syntheses is underlined by an in situ pair distribution function analysis of cluster formation, which showed that the [Zr 6 O 4 (OH) 4 (RCO 2 ) 12 ] SBU that underpins most Zr MOFs can form in solution prior to ligand incorporation. 43 Any additional modulator or ligand source that enhances this pre-clustering will likely increase reaction rates and modify particle sizes.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…[1][2][3] Since the majority of MOF syntheses is carried out starting from liquid reaction mixtures, the formation of the solid product can be followed in situ employing scattering techniquessuch as X-ray diffraction (XRD), [4][5][6][7][8] small angle X-ray scattering (SAXS), [9][10][11] static/dynamic light scattering (SLS/DLS), [12][13] -or turbidity measurements. [14][15] SAXS, SLS/DLS and turbidity are especially suited to study the earliest stages of crystallisation because they can detect particles with subnanometric size, but they provide no information about the crystal structure of the scattering objects. 1 On the other hand, XRD is limited to crystallites having size at least in the nanometre range and is blind to amorphous matter, making it not suitable for studying the earliest stages of crystallisation.…”
Section: Introductionmentioning
confidence: 99%